Examination of Hybrid-specific nutrient supply at corn on chernozem soli - Karancsi, Lajos Gábor; Dóka, Lajos Fülöp; Pepó, Péter (Acta Agraria Debreceniensis, 2012)
The effect of increasing fertilizer dosages on the yield of eight different maize hybrids (SY Ondina, NK Kansas, NK Lucius, NK Octet, NK Thermo, SY Flovita, SY Brillio, NX 47279) has been investigated in the crop-year of 2011. According to our results it can be stated that contrarily to the control treatment the application of different nutrient-levels has resulted a significant yield increment (2 000–5 800 kg ha-1). Based upon the results of this experiment we have drawn the conclusion that the nutrient level of 120 kg N+PK was the optimal for the investigated hybrids. The highest yield (14 475 kg ha-1–15 963 kg ha-1) of the hybrids with different genotypes has been produced in case of this fertilizer treatment. With the comparison of the control and the optimum-fertilizer treatments the yield-increasing effect of mineral fertilization and the different reaction of hybrids towards increasing fertilizer dosages have been proven. In case of the control treatments the best-yielding hybrids were NK Thermo (11 917 kg ha-1) and NX 47279 (11 617 kg ha-1). Contrarily on the optimal nutrient supply level the hybrids SY Brillio (15 876 kg ha-1) and NX 47279 (15 963 kg ha-1) have produced the highest yields. Summarizing, we can state that the hybrid NX 47279 has resulted stable and high yields in the fertilized treatments. Analysing the yield-increasing effect of 1 kg fertilizer active substance it was proven, that the hybrids SY Flovita (45.43 kg ha-1), SY Brillio (44.47 kg ha-1) and NX 47279 (42.33 kg ha-1) had a good reaction towards even lower nutrient supply levels as well. In case of the control treatment the average water utilization coefficient of the hybrids was significantly lower (35.2 kg mm-1), than in case of the optimal nutrient supply level (N120+PK) treatments (48.9 kg mm-1). Therefore the hybrid specific difference between the water utilization of genotypes could be revealed.